(untitled) (Research, Society and Development, 2022)
The sanitary collapse caused by the disease called coronavirus started in 2020 forced public and private schools to develop their activities through remote teaching. During the transition from the face-to-face to the virtual model, not only students but also educators had to deal with new teaching practices. In this scenario, we, Physical Education teachers, became hostages to an unusual situation, improvising classes, working remotely and trying to develop, from a distance, the issues related to the Movement’s Corporal Culture. Prepared by five teachers who work in public education in six cities in the state of Rio de Janeiro, this text reflects these challenges and shows, based on experience reports, perceptions about the adversities and tensions faced during the pandemic school period. The objective is to share our knowledge of experiences through autobiographical narrative in order to contribute to more plural, democratic and inclusive pedagogical practices in Physical Education classes. Among the issues that appeared in the narratives of our collective, we highlight: the lack of training to work in a virtual environment, the uncertainty of going back to face-to-face classes, the discussion about how and what content to develop, the lack of accessibility for students with disabilities, and the lack of knowledge of the realities of the students.